Tối ưu quy trình chiết Asen trong trầm tích - Mai, Nguyễn Thị Hoa; Trang, Phạm Thị Kim; Trang, Cao Thị Mai; Trang, Nguyễn Thị Thu; Khuê, Nguyễn Như; Tươi, Hoàng Thị; Việt, Phạm Hùng; Postma, Dieke (VNU Journal of Science: Natural Sciences and Technology, 2012)
Tóm tắt: